Adverse responses of Cabera pusaria caterpillars to high dietary manganese concentration. Issue 8 (16th June 2020) - Martinek, Petr; Hedbávný, Josef; Kudláček, Tomáš; Šťasta, Michal; Kula, Emanuel
Abstract: The adaptation of insects to environmental changes can constitute a crucial factor in their development and activity. The response of Cabera pusaria L. (Lepidoptera: Geometridae) caterpillars to high manganese (Mn) concentrations in the diet was studied. Birch leaves were treated by dipping in MnCl2 ·4H2 O solutions, thereby achieving Mn contents of 370 (T0), 695 (T1), 3 198 (T2), and 6 302 mg kg −1 (T3). The reactions were determined by observing caterpillar mortality, development time, food consumption, and pupal weight. Manganese concentrations in larval excrement, pupae, and food were determined. Manganese in the diet at unnaturally increased concentrations caused great stress for caterpillars. All individuals in the treatment with the highest Mn concentration (T3) died during rearing and successful pupation occurred in only four individuals in T2. Even in the case of caterpillars from T1 (twofold higher than T0) a negative reaction (increased food consumption and prolonged development) was recorded. We also determined significantly increased Mn concentration in pupae from T1 (T2 and T3 were not included in this evaluation due to mortality) and excrement (T1‒T3) compared with T0 having a natural Mn concentration. Caterpillars were seen to eliminate negatively acting dietary Mn by its translocation to excrement. However, the highest mortality rate in T2 and T3 and negative reactions of individuals in T1 very likely demonstrate energy insufficiency and the high energy requirements of Mn elimination mechanisms. Abstract : The activity of Cabera pusaria (Lepidoptera: Geometridae) caterpillars continually decreased with increasing Mn content in the diet. Manganese in the diet influenced larvae despite their ability of self‐detoxification. The energy demand of the Mn self‐detoxification mechanism was a mortality factor for caterpillars on the diet with the highest contaminations of Mn.